"[T]here are known knowns … things we know that we know": Some reflections on the nature and practice of interpretive accounting research. Issue 8 (16th October 2017) - de Loo, Ivo; Lowe, Alan
Abstract : Purpose: The starting point for this paper is that the researcher is intimately bound up in all aspects of the research process. This idea of what is a critical aspect of much interpretive methodology has been challenged by some proponents of the interpretive accounting research (IAR) project. The authors suggest that adopting some of the views expounded in the IAR project may lead to the accounting research community becoming isolated from other interpretive methodology inspired disciplines. The paper aims to discuss these issues. Design/methodology/approach: Currently popular views on IAR are informed by selective theoretical insights from interpretive sociology. The authors argue that these insights cannot provide a general frame with which to encapsulate accounting research that may be reasonably termed "interpretive." Findings: The authors' reading of the literature suggests that the some of the IAR literature exhibits: a tendency to routinely make overly specific claims for what it is possible for interpretive research to achieve; the promotion of a somewhat reductionist view of what the bounds of interpretive research are. The authors suggest that these tendencies detract from the strengths of (adopting a broad view of) IAR. Research limitations/implications: In expressing the authors' concerns, the authors do not wish to make an exclusive argument for what IAR is and is not. This would not be in line with writing an interpretive paper. While the authors do not eschew the possibility of a limited building of knowledge by applying interpretive methodological stances neither do the authors see such activity as a central plank of interpretive research. Practical implications: The authors believe that positivistic commentaries on qualitative enquiry should not be taken as exemplary of interpretive research (in accounting – or elsewhere). The authors feel that IAR needs to be more open to an array of subjectivist motivations, if it is to provide useful critique of the nature of day-to-day accounting practice. Originality/value: The authors seek to go beyond the rather unhelpful debate about whether IAR should be seen to possess both objective and subjective elements. The authors argue that IAR suffers more from a lack of engagement and debate than it faces dangers from areas of interpretive methodology that adopt positions considered to be too subjectivist.